From 2-phenylbenzoxazole to diphenyl-bibenzoxazole derivatives: Comparative advantages of mono- and bis-chromophores for solution and solid-state fluorescence. (February 2016) - Ghodbane, Abdelhamid; Bordat, Patrice; Saffon, Nathalie; Blanc, Sylvie; Fery-Forgues, Suzanne
Abstract: The optical properties of three bis-benzoxazole derivatives, namely 2, 2'-diphenyl-6, 6'-bibenzoxazole and its derivatives bearing methyl and tert -butyl groups at the para position, were investigated and compared to those of the corresponding subunits. As expected from the increase of the π-electron conjugated system, the absorption and fluorescence spectra were red-shifted when passing from mono-to bis-chromophores. The three bis-benzoxazoles showed superior fluorescence quantum yields in solution, but they were only weakly emissive in the solid state, the unsubstituted derivative even being virtually not photoluminescent. The solid-state behaviour was explained by the fact that bis-chromophoric molecules were locked in a non-planar conformation, as discussed on the basis of DFT calculations and X-ray data. Highlights: 2-Phenylbenzoxazoles were well fluorescent in solution and in the solid state. Bis-benzoxazoles had superior emission in solution. In the solid state, their twisted conformation was a disadvantage for photoluminescence. Graphical abstract: